A clinical validation of the MR‐compatible Delta4 QA system in a 0.35 tesla MR linear accelerator. Issue 4 (5th March 2021) - Desai, Vimal; Bayouth, John; Smilowitz, Jennifer; Yadav, Poonam
Abstract: Purpose: To validate an MR‐compatible version of the ScandiDos Delta 4 Phantom+ on a 0.35T MR guided linear accelerator (MR‐Linac) system and to determine the effect of plan complexity on the measurement results. Methods/Materials: 36 clinical treatment plans originally delivered on a 0.35T MR linac system were re‐planned on the Delta 4 Phantom+ MR geometry following our clinical quality assurance (QA) protocol. The QA plans were then measured using the Delta 4 Phantom+ MR and the global gamma pass rates were compared to previous results measured using a Sun Nuclear ArcCHECK‐MR. Both 3%/3mm and 2%/2mm global gamma pass rates with a 20% dose threshold were recorded and compared. Plan complexity was quantified for each clinical plan investigated using 24 different plan metrics and each metric's correlation with the overall 2%/2mm global gamma pass rate was investigated using Pearson correlation coefficients. Results: Both systems demonstrated comparable levels of gamma pass rates at both the 3%/3mm and 2%/2mm level for all plan complexity metrics. Nine plan metrics including area, number of active MLCs, perimeter, edge metric, leaf segment variability, complete irradiation area outline, irregularity, leaf travel index, and unique opening index were moderately (|r| > 0.5) correlated with the Delta 4 2%/2mm global gamma pass rates whereas those same metrics had weak correlation with the ArcCHECK‐MR pass rates. Only the perimeter to area ratio and small aperture score (20 mm) metrics showed moderate correlation with the ArcCHECK‐MR gamma pass rates. Conclusions: The MR‐compatible version of the ScandiDos Delta 4 Phantom+ MR has been validated for clinical use on a 0.35T MR‐Linac with results being comparable to an ArcCHECK‐MR system in use clinically for almost five years. Most plan complexity metrics did not correlate with lower 2%/2mm gamma pass rates using the ArcCHECK‐MR but several metrics were found to be moderately correlated with lower 2%/2mm global gamma pass rates for the Delta 4 Phantom+ MR.